Fourth Indexing Course - DESIDOC, Director (DESIDOC Journal of Library & Information Technology, 2002)
The fourth training course in 'Indexing' was organised by DESIDOC at Metcalfe House, Delhi from 24 Feb to 6 Mar 1982. The course was intended for information personnel of DRDO Labs/Estts located in the north zone. The curriculum covered various aspects of indexing techniques and systems including computer processing. Besides the lectures and practical assignments, audiovisual demonstration on NTIS services was also screened. Visits to DRDO Computer Centre to familiarise the participants with the working of the computer, and INSDOC/National Science Library were also arranged.